2018
DOI: 10.1101/428052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The social situation affects how we process feedback about our actions

Abstract: Humans achieve their goals in joint action tasks either by cooperation or competition. In the present study, we investigated the neural processes underpinning error and monetary rewards processing in such cooperative and competitive situations. We used electroencephalography (EEG) and analyzed event-related potentials (ERPs) triggered by feedback in both social situations. 26 dyads performed a joint four-alternative forced choice (4AFC) visual task either cooperatively or competitively. At the end of each tria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For instance, a future study could assess the role of verbal communication as opposed to receiving action information in predicting group benefits. Other non-redundant predictors might include personality traits of the group members, e.g., those relevant to social cognition such as empathy (Czeszumski et al, 2019;Davis, 1983). Moreover, future studies could test to what extent the predictors used in the present model are applicable to other joint tasks.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a future study could assess the role of verbal communication as opposed to receiving action information in predicting group benefits. Other non-redundant predictors might include personality traits of the group members, e.g., those relevant to social cognition such as empathy (Czeszumski et al, 2019;Davis, 1983). Moreover, future studies could test to what extent the predictors used in the present model are applicable to other joint tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Another set of predictors for which the contribution towards predicting group benefits in joint visuospatial tasks has not been assessed are personality traits relevant for social interactions (e.g., empathy) and the interpersonal relation between co-actors (i.e., to what extent they know each other). In particular, previous research found significant correlations between personality traits related to empathy (assessed with the Interpersonal Reactivity Index questionnaire (Davis et al, 1980)) and joint performance (Ford and Aberdein, 2015) or neurophysiological correlates of error processing in joint tasks (Czeszumski et al, 2019;Koban et al, 2012;Ruissen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, little research has explored if the coordination associated with labor division is related to physiological correlates of mental effort while physiological correlates in joint tasks of, for instance, error processing (Czeszumski et al, 2019;Loehr et al, 2013), decision-making (Baumgart et al, 2020) or leader-follower dynamics (Konvalinka et al, 2014) have been explored.…”
Section: Introductionmentioning
confidence: 99%